2012
DOI: 10.7202/1008539ar
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenicity of Pythium species causing seed rot and damping-off in soybean under controlled conditions

Abstract: Montréal. Il a pour mission la promotion et la valorisation de la recherche. Érudit offre des services d'édition numérique de documents scientifiques depuis 1998.Pour communiquer avec les responsables d'Érudit : info@erudit.org Article "Pathogenicity of Pythium species causing seed rot and damping-off in soybean under controlled conditions" Lai Wei, Allen G. Xue, Elroy R. Cober, Carolyn Babcock, Jinxiu Zhang, Shuzhen Zhang, Wenbin Li, Junjiang Wu et Lijun Liu Phytoprotection, vol. 91, 2010Phytoprotection, vol.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…Pythium sylvaticum was the most prevalent species detected across the midwestern United States on diseased soybean seedlings ( Broders et al, 2007 ; Wei et al, 2010 ; Jiang et al, 2012 ; Rojas et al, 2017 ). We used this species to test for resistance in three of our four populations (POP1, POP3, and POP4).…”
Section: Discussionmentioning
confidence: 99%
“…Pythium sylvaticum was the most prevalent species detected across the midwestern United States on diseased soybean seedlings ( Broders et al, 2007 ; Wei et al, 2010 ; Jiang et al, 2012 ; Rojas et al, 2017 ). We used this species to test for resistance in three of our four populations (POP1, POP3, and POP4).…”
Section: Discussionmentioning
confidence: 99%
“…Among the tested isolates, GZ-11 isolate was found to be the highest pathogenic, causing seed rot and seedling damping-off at rate 100%, and selected to be identified. Wei et al (2011) in study with eight Pythium spp reported that Pythium ultimum was the most pathogenic species resulting in 97% seed rot and 46.4% damping-off on soybean. Rossman et al (2017) observed variations in the virulence of the Pythium isolates in causing seed rot and pre-emergence damping-off of dry bean.…”
Section: Pathogenicity Of Pythium Sppmentioning
confidence: 98%
“…Because longer growing seasons directly correlate with increased soybean yields, early planting is the current preferred practice ( Rowntree et al, 2013 ). However, cold soils, coupled with an unseasonably wet planting season, increases the risk of oomycete-mediated root rot seedling loss ( Broders et al, 2007 ; Wei et al, 2011 ; Zitnick-Anderson and Nelson, 2015 ). Direct sampling of infected plants found that a wide range of pathogens were involved.…”
Section: Introductionmentioning
confidence: 99%
“…Some of these Pythium species such as P. irregulare, P. sylvaticum, P. torulosum , and P. macrosporum were cold adapted and most aggressive at soil temperatures below 20°C. Other species such as P. ultimum infect different hosts at temperatures ranging from 12 to 25°C ( Wei et al, 2011 ), while P. aphanidermatum cause soybean seedling rot only at temperatures of 20–25°C ( Rojas et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%